2010
DOI: 10.1126/science.1191078
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Signals of Epigenetic States

Abstract: Epigenetic signals are responsible for the establishment, maintenance and reversal of metastable transcriptional states that are fundamental for the cell's ability to “remember” past events, such as changes in the external environment or developmental cues. Complex epigenetic states are orchestrated by several converging and reinforcing signals, including transcription factors, non-coding RNAs, DNA methylation, and histone modifications. Although all these pathways modulate transcription from chromatin in vivo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
657
1
15

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 831 publications
(677 citation statements)
references
References 86 publications
4
657
1
15
Order By: Relevance
“…However, certainly not all modifications are "epigenetic", because many of them may not be inheritable as required under a widely accepted definition of "epigenetics" [1,4]. In fact, even for methylated versions of H3K9 and H3K27 that play critical roles in well-studied epigenetic phenomena, including position effect variegation, Polycomb silencing and X chromosome inactivation in mammals [5][6][7][8][9][10][11][12][13], it is not clear whether these modifications are faithfully reestablished on the newly deposited histones.…”
Section: Replication-independent Modification "Maturation" On Newly Dmentioning
confidence: 99%
See 1 more Smart Citation
“…However, certainly not all modifications are "epigenetic", because many of them may not be inheritable as required under a widely accepted definition of "epigenetics" [1,4]. In fact, even for methylated versions of H3K9 and H3K27 that play critical roles in well-studied epigenetic phenomena, including position effect variegation, Polycomb silencing and X chromosome inactivation in mammals [5][6][7][8][9][10][11][12][13], it is not clear whether these modifications are faithfully reestablished on the newly deposited histones.…”
Section: Replication-independent Modification "Maturation" On Newly Dmentioning
confidence: 99%
“…The current definition of "epigenetics" is "the inheritance of variation (-genetics) above and beyond (epi-) changes in the DNA sequence" [1]. In eukaryotic cells, the basic unit of chromatin is the nucleosome, composed of 147 bp of DNA wrapped around the core histone octamer [2].…”
Section: Introductionmentioning
confidence: 99%
“…During fetal development, environmental cues can induce the modification of a pliable epigenome, which can result in long-term changes in gene expression that occur in a self-sustaining manner in the absence of the original stimulus. 5 Adverse gestational conditions that arise from inadequate healthcare, poor nutrition, socioeconomic disadvantage and racial disparities are often associated with long-lasting phenotypic consequences in adults, yielding greater risk of diabetes and heart disease, 6,7 as well as low birth weight and congenital defects in progeny. [8][9][10] It is now becoming evident that these effects are inextricably linked to altered epigenetic patterns.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies showed that the Jumonji C-containing protein Jarid2 associates with PRC2, and this association enables both Jarid2 and PRC2 to access their respective target genes in embryonic stem (ES) cells (Peng et al 2009;Shen et al 2009;Landeira et al 2010;Li et al 2010;Pasini et al 2010). In addition, several noncoding RNAs (ncRNAs) have been found to bind PRC2 (Zhao et al 2008;Kanhere et al 2010;Tsai et al 2010), one of which, HOTAIR, is expressed from the HOXC cluster but recruits PRC2 to the HOXD cluster, thereby regulating transcriptional repression of these genes in trans (Rinn et al 2007;Bonasio et al 2010). Additionally, the ncRNA Xist, which is expressed from the female X chromosome directed to undergo X inactivation, was suggested to bind to and recruit the PRC2 complex in cis.…”
mentioning
confidence: 99%